2016
DOI: 10.1002/2015ja022244
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise tailward retreat of magnetic reconnection: THEMIS observations of an auroral substorm

Abstract: Auroral stepwise poleward expansions were clarified by investigating a multiple‐onset substorm that occurred on 27 February 2009. Five successive auroral brightenings were identified in all‐sky images, occurring at approximately 10 min intervals. The first brightening was a faint precursor. The second brightening had a wide longitude; thus, it represented the Akasofu substorm onset. Other brightenings expanded poleward; thus, they were interpreted to be auroral breakups. These breakups occurred stepwise; that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 105 publications
2
14
1
Order By: Relevance
“…Since the existence of detailed ionospheric structure during the onset is an observational fact, if the corresponding structure is shown in the magnetosphere, it should certainly help to make the cause of the onset clearer. In traditional substorm theories, detailed sequence of the onset is attributed to the dynamical wandering of reconnection point in the equatorial plane [Kadokura et al, 2002;Saito et al, 2010;Ieda et al, 2016]. In this paper, we try to give another explanation applying the near-Earth dynamo associated with the convection transient.…”
Section: Detailed Structure Of the Onsetmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the existence of detailed ionospheric structure during the onset is an observational fact, if the corresponding structure is shown in the magnetosphere, it should certainly help to make the cause of the onset clearer. In traditional substorm theories, detailed sequence of the onset is attributed to the dynamical wandering of reconnection point in the equatorial plane [Kadokura et al, 2002;Saito et al, 2010;Ieda et al, 2016]. In this paper, we try to give another explanation applying the near-Earth dynamo associated with the convection transient.…”
Section: Detailed Structure Of the Onsetmentioning
confidence: 99%
“…Recent simulation studies that reproduce plasma sheet dynamics leading to the substorm onset have shown the increasing ability of global simulation for the substorm study [Wiltberger et al, 2000;Tanaka, 2000;Tanaka et al, 2010;Ge et al, 2011;El-Alaoui et al, 2016]. It is found from more recent studies that increasing the resolution of FAC calculation in the global simulation, the simulation model exerts the ability to reproduce a realistic substorm not only in the magnetosphere but also in the ionosphere [Tanaka, 2015;Ebihara and Tanaka, 2015a, 2015b, 2016. In these studies, substorm variations in the ionosphere (the preonset N-S arc, the quiet arc, the initial brightening, the WTS, etc.)…”
Section: Substorm Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Practically, precursor brightenings are often observed prior to the AIB (e.g., Ieda et al. 2016). It is sometimes difficult to determine whether such a brightening is the AIB or a precursor, particularly when it does not decay significantly, leading to subjectivity in the duration of the AIB.…”
Section: Discussionmentioning
confidence: 99%